2019
DOI: 10.1097/md.0000000000015336
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of HE4 expression in multiple carcinomas

Abstract: Background: Human epididymis protein 4 (HE4) protein has garnered a great degree of interest as a complementary biomarker to carbohydrate antigen 125 (CA125), or even as an independent biomarker for monitoring, diagnosis, and prognostication of ovarian cancer. Its use is currently limited to ovarian cancer. Recent studies have suggested that it could also be used in other types of cancers. Methods: The Preferred Reporting Items for Systematic Review and Meta-Analysis Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…According to the criteria of the GRADE guideline, there was one high-quality evidence, Dai et al ( 44 ) conducted a meta-analysis and reported that the HE4 level can provide a useful prognostic biomarker (only for DFS) for patients with cancers (987 patients with EC, 211 patients with LC, and 98 patients with OC). The prognostic effect of HE4 on the disease was mainly focused on OC, but a systematic review suggested that the prognostic role of HE4 in other types of cancers needed more endeavor than before ( 55 ). Previous articles or meta-analyses suggested that OC ( 23 , 56 ), EC ( 57 ), LC ( 58 ), and GC ( 59 ) patients with a high concentration of HE4 have shorter survival or more likely metastasis than those with low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the criteria of the GRADE guideline, there was one high-quality evidence, Dai et al ( 44 ) conducted a meta-analysis and reported that the HE4 level can provide a useful prognostic biomarker (only for DFS) for patients with cancers (987 patients with EC, 211 patients with LC, and 98 patients with OC). The prognostic effect of HE4 on the disease was mainly focused on OC, but a systematic review suggested that the prognostic role of HE4 in other types of cancers needed more endeavor than before ( 55 ). Previous articles or meta-analyses suggested that OC ( 23 , 56 ), EC ( 57 ), LC ( 58 ), and GC ( 59 ) patients with a high concentration of HE4 have shorter survival or more likely metastasis than those with low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Kumarasamy et al 21 review, the possibility of using HE4 as a prognostic marker has not been adequately explored. Looking at the Lan et al 22 results, the normalization of CA125 level in serum after three cycles of chemotherapy may predict the favorable outcome of patients with advanced ovarian cancer if it was pathologic at the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed in the serum of patients with malignant tumors but may be increased in varying degrees in the serum of benign lesions or healthy patients. HE4 has been recently identified as a potential biomarker in endometrial carcinoma (3,4,27,28). Some studies (3,5,(29)(30)(31)(32)(33) showed that CA125 and HE4 were significantly correlated with histological grade, stage, lymph node metastasis, muscular invasion, and cervical involvement.…”
Section: Introductionmentioning
confidence: 99%